(untitled) (JURNAL PENGMAS KESTRA (JPK), 2025)
Typhoid fever remains a significant public health problem in Indonesia and is primarily caused by infection with Salmonella typhi through contaminated food and beverages. The high incidence of typhoid is closely associated with inadequate clean and healthy living behaviors and limited access to preventive health measures. In addition, irrational use of antibiotics may contribute to bacterial resistance, highlighting the need for safer, natural-based antibacterial alternatives. The ketapang plant (Terminalia catappa L.) is widely found in residential areas and is known to contain secondary metabolites such as flavonoids, tannins, and saponins with potential antibacterial activity; however, its utilization among communities remains limited. This community service program aimed to enhance public knowledge and understanding of the utilization of ketapang leaves as a natural antibacterial agent in the prevention of typhoid fever. The program employed an educative–participatory approach involving educational sessions, interactive discussions, and simple demonstrations, with 30 participants from Lubuk Pakam District. Knowledge improvement was evaluated using pre-test and post-test questionnaires. The results demonstrated a significant increase in participants’ knowledge, indicated by a reduction in the low-knowledge category from 56.7% to 10.0% and an increase in the high-knowledge category to 70.0%. The mean knowledge score increased from 56.2 to 85.4, with a difference of 29.2 points. Participant engagement and satisfaction were also high, with an average satisfaction level of 91.7%. Overall, this community service activity was effective in improving knowledge, participation, and community acceptance of ketapang plant utilization as a promotive and preventive health effort based on local resources.